Fast and smooth trajectory planning for a class of linear systems based on parameter and constraint reduction - Liu, Guangyu; Wu, Shangliang; Zhu, Ling; Wang, Jiajun; Lv, Qiang (Zielona Góra: Uniwersytet Zielonogórski)
Fast and smooth trajectory planning is crucial for modern control systems, e.g., missiles, aircraft, robots and AGVs. However, classical spline based trajectory planning tools introduce redundant constraints and parameters, leading to high costs of computation and complicating fast and smooth execution of trajectory planning tasks. A new tool is proposed that employs truncated power functions to annihilate some constraints and reduce the number of parameters in the optimal model. It enables solving a simplified optimal problem in a shorter time while keeping the trajectory sufficiently smooth. With an engineering background, our case studies show that the proposed method has advantages over other solutions. It is promising in regard to the demanding tasks of trajectory planning.
Keywords: constraint reduction; parameter reduction; fast calculation; trajectory planning